Out of Africa: Exploring the African germplasm for the sustainable production of rice in future climates - Cowling, Sophie (2022)
Asian rice (Oryza sativa) is a staple food for billions of people worldwide. There has been increasing focus on the introgression of diverse material to develop productive rice cultivars that are resilient to a changing climate. African rice (Oryza glaberrima) evolved independently to Asian rice and demonstrates exceptional abiotic stress resilience. O. glaberrima has been recognised as a potential source for crop improvement for over two decades but the heritable variation in the species remains relatively uncharacterised. The research described here uses a new genomic resource of 155 re-sequenced accessions to explore the diversity O. glaberrima has to offer.